Synthesis, structure, and air-stable N-type field-effect transistor behaviors of functionalized octaazanonacene-8,19-dione - Wang, Chengyuan (2015)
Increasing the length of N-heteroacenes or their analogues is highly desirable because such materials could have great potential applications in organic electronics. In this report, the large π-conjugated N-heteroquinone 6,10,17,21-tetra-((triisopropylsilyl)ethynyl)-5,7,9,11,16,18,20,22-octaazanonacene-8,19-dione (OANQ) has been synthesized and characterized. The as-prepared OANQ shows high stability under ambient conditions and has a particularly low LUMO level, which leads to it being a promising candidate for air-stable n-type field-effect transistors (FETs). In fact, FET devices based on OANQ single crystals have been fabricated and an electron mobility of up to 0.2 cm2 V−1 s−1 under ambient conditions is reported. More importantly, no obvious degradation was observed even after one month. Theoretical calculations based on the single crystal are consistent with the measured mobility.